Kilmacreehy church, north chancel wall, tomb niche, hood - O'Donovan, Danielle (My University, 2008)
Hood mould of tomb niche, from outside in the moulding comprises: frontal fillet, fillet, roll-and-fillet, fillet, hollow, flat surface running into wall.
Keywords: Architecture, Gothic -- Ireland; Clare (Ireland)--Antiquities.; Funerary monuments; Late Medieval; roll-and-fillet moldings; moldings, hollow